Proximity of Substantia Nigra Microstimulation to Putative GABAergic Neurons Predicts Modulation of Human Reinforcement Learning - Ramayya, Ashwin G.; Pedisich, Isaac; Levy, Deborah; Lyalenko, Anastasia; Wanda, Paul; Rizzuto, Daniel; Baltuch, Gordon H.; Kahana, Michael J. (Frontiers in Human Neuroscience, 2017)
4 Neuronal firing in the substantia nigra (SN) immediately following reward is thought to play 5 a crucial role in human reinforcement learning. As in Ramayya et al., (2014) we applied 6 microstimulation in the SN of patients undergoing deep brain stimulation (DBS) for the treatment 7 of Parkinson’s disease as they engaged in a two-alternative reinforcement learning task. We 8 obtained microelectrode recordings to assess the proximity of the electrode tip to putative 9 dopaminergic and GABAergic SN neurons and applied stimulation to assess the functional 10 importance of these neuronal populations for learning. We found that the proximity of SN 11 microstimulation to putative GABAergic neurons predicted the degree of stimulation-related 12 changes in learning. These results extend previous work by supporting a specific role for SN 13 GABA firing in reinforcement learning. Stimulation near these neurons appears to dampen the 14 reinforcing effect of rewarding stimuli.